Optimising communication with Ddeaf patients during the COVID-19 pandemic: A case study.: International Summer Conference: Inequalities in Medicine, In2MedSchool (I2MS), 2nd July 2022. - Duck, Eleanor (Advanced Journal of Professional Practice, 2022)
Background: Deafness is defined as severe hearing loss resulting in little to no auditory perception. D/deaf individuals may use multiple methods of non-verbal communication e.g., lip-reading, sign-language, reading/writing. During the COVID-19 pandemic public health measures such as use of personal protective equipment (PPE) and strict hospital visiting policies limiting signing interpreter access, disproportionately affected the D/deaf community’s ability to communicate and thus engage with healthcare professionals. Case Study: A 76-year-old female with a background of bilateral hip osteoarthritis and low mood was admitted to a community hospital for rehabilitation following a fall. She was congenitally deaf and communicated by British Sign Language (BSL), reading/writing and lip reading. On the 9th day of admission, she became symptomatic of COVID-19 infection with cough, fever, tachypnoea, and she tested positive on PCR. According to infection control protocol she was required to isolate for 10 days. During this time the patient reported worsening mood and struggled to engage with rehabilitation exercises without her regular BSL interpreter to assist with instructions. Discussion: As per the Equality Act 2010 the NHS has a duty to make reasonable adjustments to enable communication between D/deaf patients and healthcare professionals. However, almost 90% of D/deaf people report being worried about how they will communicate if hospitalised with COVID-19. The current evidence on the impact of COVID-19 on D/deaf people and strategies to improve in-hospital communication was explored.